Runoff Characterization and Variations at McMurdo Station, Antarctica - Affleck, Rosa T; Carr, Meredith; Knuth, Margaret; Elliot, Laura; Chan, Corey; Diamond, Michael (2014)
As the austral summer approaches, major flow arteries are manually cleared in anticipation of the ephemeral runoff during the summer months. This flow, primarily from snowmelt, has daily and seasonal fluctuations. The flow fluctuation and variation depend on the air temperature and on many other factors. In addition, the runoff mobilizes sediment and localized soil contaminants that wash through these channels and discharge primarily into Winter Quarters Bay. This report quantifies the runoff characteristics, including discharge correlations and variations for McMurdo Station drainage channels, and expands our understanding on the runoff characteristics at McMurdo Station. The flow data taken during austral summer 2010 11 combined with 2009 10 data fills the gaps in the analysis to quantify the runoff. Based on the correlation between the change in accumulated thawing degree days and cloudiness expressed in clearness, the time delay in the peak discharge can occur between 4 and 14 days after a peak temperature. Based on the frequency and probability distribution of the flow, a flow greater than 0.33 m3/s in the major channel occurred less than 5% of the time during the season. This study provides critical information for planning, operation and maintenance, the design of preventive methods, and the application of best practices. The original document contains color images. Prepared in collaboration with the Antarctic Support Contract, Centennial, CO, and the University of Vermont, Burlington.